(untitled) (Journal of Engineering, 2023)
The central marshes are one of the most important wetlands/ecosystems in the southern area of Iraq. This study evaluates the bed soil’s mechanical, physical, and chemical properties at certain southern Iraqi central marshes sites. This was conducted to investigate their types and suitability for enhancing the agricultural reality of most field crops and for construction purposes. Soil samples were collected from 15 sites at 10-100 cm depth. Hence, numerous parameters were determined: index properties, unconfined compressive strength, direct shear strength, consolidation, texture, and sieve analysis, water content, specific gravity, dry density, permeability, pH, total soluble salts (TSS), organic materials (OM) and total sulfate content SO3. Results of this study showed that the bed soil of the Central Marshes is classified as clay-silt soil and suitable for planting different crops. Furthermore, Analysis of the results may have a role in the design and planning of upcoming projects, such as the construction of buildings and agriculture, that would have to enlighten the decision maker.